Covalent Organic Framework Embedded with Magnetic Nanoparticles for MRI and Chemo-Thermotherapy - Benyettou, Farah; Das, Gobinda; Nair, Anjana Ramdas; Prakasam, Thirumurugan; Shinde, Digambar B; Sharma, Sudhir Kumar; Whelan, Jamie; Lalatonne, Yoann; Traboulsi, Hassan; Pasricha, Renu; Abdullah, Osama; Jagannathan, Ramesh; et al. (Journal of the American Chemical Society, 2020)
Nanoscale imine-linked covalent organic frameworks (nCOFs) were first loaded with the anticancer drug Doxorubicin (Dox), coated with magnetic iron oxide nanoparticles (γ-Fe2O3 NPs), and stabilized with a shell of poly(l-lysine) cationic polymer (PLL) for simultaneous synergistic thermo-chemotherapy treatment and MRI imaging. The pH responsivity of the resulting nanoagents (γ-SD/PLL) allowed the release of the drug selectively within the acidic microenvironment of late endosomes and lysosomes of cancer cells (pH 5.4) and not in physiological conditions (pH 7.4). γ-SD/PLL could efficiently generate high heat (48 °C) upon exposure to an alternating magnetic field due to the nCOF porous structure that facilitates the heat conduction, making γ-SD/PLL excellent heat mediators in an aqueous solution. The drug-loaded magnetic nCOF composites were cytotoxic due to the synergistic toxicity of Dox and the effects of hyperthermia in vitro on glioblastoma U251-MG cells and in vivo on zebrafish embryos, but they were not significantly toxic to noncancerous cells (HEK293). To the best of our knowledge, this is the first report of multimodal MRI probe and chemo-thermotherapeutic magnetic nCOF composites.